Metode Komunikasi PUSBAKUM Silampari di Pengadilan Negeri Lubuk Linggau dalam Upaya Perlindungan Anak - Sopiyan, Wawan - (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This study aims to analyze the communication methods of PUSBAKUM Silampari in the Lubuklinggau District Court and identify its contribution to child protection efforts. The background of this research is based on the complexity of child protection cases that require an effective and sensitive communicative approach. The research method is descriptive with a focus on the description of the communication method of PUSBAKUM Silampari and the evaluation of its effectiveness. The literature review outlines the principles of child protection and the role of PUSBAKUM Silampari in the context of the judicial system. This study involves a population of child protection cases handled by the Lubuklinggau District Court, with a sample of cases involving the communication method of PUSBAKUM Silampari. The data collection method involves interviews with related parties, document analysis, and direct observation of the communication process of PUSBAKUM Silampari. Data analysis was carried out qualitatively to understand the characteristics of communication methods and their effectiveness in the context of child protection. The results of the study show that the communication method of PUSBAKUM Silampari has special characteristics that support the achievement of child protection goals. The success of this method is reflected in the increase in understanding and cooperation between parties involved in the judicial process. The implications of this study include recommendations for strengthening training and the development of similar communication methods in other courts. Thus, this research makes an important contribution to our understanding of the role of communication in the context of child protection in the Lubuklinggau District Court. Its practical implications could guide improvements in judicial policies and practices that focus on the welfare of children involved in the justice system.